2018
DOI: 10.3390/s18092953
|View full text |Cite
|
Sign up to set email alerts
|

Application of PZT Technology and Clustering Algorithm for Debonding Detection of Steel-UHPC Composite Slabs

Abstract: A lightweight composite bridge deck system composed of steel orthotropic deck stiffened with thin Ultra-High Performance Concrete (UHPC) layer has been proposed to eliminate fatigue cracks in orthotropic steel decks. The debonding between steel deck and UHPC layer may be introduced during construction and operation phases, which could cause adverse consequences, such as crack-induced water invasion and distinct reduction of the shear resistance. The piezoelectric lead zirconate titanate (PZT)-based technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Piezoceramic transducers have the advantages of both sensing and actuation capacities [36,37], high bandwidth [38,39], and low cost, and have been actively studied to monitor debonding problems in various structures [40,41,42,43], including rebar and concrete debonding [44,45,46]. In addition, in the form of a smart aggregate, a piezoceramic transducer can be easily and reliably embedded in a concrete structure [47,48], or in the form of a patch, a piezoceramic transducer can be surface-bonded on a structure of interest [49,50], including a steel rebar or a composite rebar.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoceramic transducers have the advantages of both sensing and actuation capacities [36,37], high bandwidth [38,39], and low cost, and have been actively studied to monitor debonding problems in various structures [40,41,42,43], including rebar and concrete debonding [44,45,46]. In addition, in the form of a smart aggregate, a piezoceramic transducer can be easily and reliably embedded in a concrete structure [47,48], or in the form of a patch, a piezoceramic transducer can be surface-bonded on a structure of interest [49,50], including a steel rebar or a composite rebar.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,19]. Monitoring of dressing operations conducted so far follows the same framework reported in the literature [20,21]. However, few studies were focused on the monitoring of dressing tool health in terms of wear, damage and breakage of dressing tools made of diamond [28,29].…”
Section: Dressing Operation Monitoringmentioning
confidence: 99%
“…In addition, recent studies showed that the implementation of a network of PZTs in the EMI technique instead of a single PZT transducer provides more accurate results concerning the detection and the evaluation of damage in structural members constructed by concrete slabs and reinforced concrete [15,16,17,18,19], and composite slabs [20,21], by using smart interface and numerical modelling to achieve the most sensitive features. On the other hand, in [22] an innovative EMI incorporating an artificial neural network (ANN)-based pattern analysis tool was proposed to identify damage-sensitive frequency ranges autonomously and to provide detailed information, such as the damage type and severity in a simply supported aluminum beam.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the complexity of the propagation phenomenon strongly depends on the debonding location, while the average wave velocity depends only on its length. Yan et al [21] employed an impedance analysis and wave propagation to identify the debondings of various thicknesses and sizes in steel ultra-high performance concrete (UHPC) composite slabs. Zhao et al [22] applied the TR method to detect and localize the defects along the steel-concrete interface.…”
Section: Introductionmentioning
confidence: 99%